1999
DOI: 10.1136/ip.5.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a street barrier on urban crime

Abstract: Objectives-Violence is a major urban public health problem in the United States. The impact of a physical barrier placed across a street in a public housing project to prevent street violence and drug activity was evaluated. Methods-Hartford Police Department data on violent and drug related crime incidence within the housing project containing the barrier were analyzed by use of a computerized geographic information system. Results-Violent crime decreased 33% on the intervention street during the 15 month per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Firstly, developments with high levels of through-movement provide ease of entry and escape for potential offenders (Rubenstein et al, 1980;Taylor and Gottfredson, 1987;Poyner and Webb, 1991). The operation of this mechanism has been demonstrated through the crime reductions observed following physical changes to the layout of existing residential areas, such as the closure of streets (Matthews, 1992;Atlas and LeBlanc, 1994;Newman, 1995Newman, , 1996Lasley, 1998;Zavoski et al, 1999, Eck, 2002. Secondly, developments with high levels of throughmovement are more likely to fall within the activity space, and therefore awareness space, of potential offenders (Brantingham and Brantingham, 1984) with offenders selecting targets properties as they take part in day to day activities (Letkemann, 1973;Feeney, 1986;Gabor et al, 1987;Poyner and Webb, 1991;Rengert and Wasilchick, 2000;Wiles and Costello 2000).…”
Section: Connectivity and Through-movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, developments with high levels of through-movement provide ease of entry and escape for potential offenders (Rubenstein et al, 1980;Taylor and Gottfredson, 1987;Poyner and Webb, 1991). The operation of this mechanism has been demonstrated through the crime reductions observed following physical changes to the layout of existing residential areas, such as the closure of streets (Matthews, 1992;Atlas and LeBlanc, 1994;Newman, 1995Newman, , 1996Lasley, 1998;Zavoski et al, 1999, Eck, 2002. Secondly, developments with high levels of throughmovement are more likely to fall within the activity space, and therefore awareness space, of potential offenders (Brantingham and Brantingham, 1984) with offenders selecting targets properties as they take part in day to day activities (Letkemann, 1973;Feeney, 1986;Gabor et al, 1987;Poyner and Webb, 1991;Rengert and Wasilchick, 2000;Wiles and Costello 2000).…”
Section: Connectivity and Through-movementmentioning
confidence: 99%
“…The table below summarises the literature reviewed on the impact of through-movement on levels of crime within residential developments, highlighting the dominance of studies concluding that higher levels of through movement increase the risk of crime. Armitage (2006) Being located on a travel path increases the risk of crime Letkemann (1973) Brantingham (1984) Feeney (1986) Gabor et al (1987) Poyner andWebb (1991) Wiles and Costello (2000) Rengert and Wasilchick (2000) Being located on a culs-de-sac, or a development with low connectivity, reduces the risk of crime Bevis and Nutter (1977) Johnson and Bowers (2010) Closing off streets reduces crime Matthews (1992) Atlas and LeBlanc (1994) Newman (1995Newman ( ,1996 Lasley (1998) Zavoski et al (1999) Eck (2002 Being located on a leaky culs-de-ac increases the risk of crime Hillier (2004) Armitage (2006) Being located on a development with high levels of permeability/connectivity/through movement reduces the risk of crime Hillier and Shu (1998) Shu (2000) Hillier (2004) Hillier and Sahbaz (2009) The review of policy and guidance documents revealed several areas of contention regarding through-movement and connectivity. Manual for Streets (Department for Transport, 2007) highlights that street networks should be connected to encourage walking and cycling and that connectivity within and between developments is important.…”
Section: Connectivity and Through-movementmentioning
confidence: 99%
“…For example, violent crimes tend to occur more on streets that are more accessible (8,82). One study by Zavoski et al (90) evaluated the impact of a single street barrier constructed by the Hartford Housing Authority in response to a drive-by shooting that wounded four teenagers near a large housing project. The study compared levels of crime incidents during the 15 months before and after the introduction of the street barrier.…”
mentioning
confidence: 99%
“…Several studies found that being located on a true cul-de-sac (with no pedestrian and vehicular connections) reduced the risk of victimisation (Armitage, 2006;Armitage et al, 2011;Johnson and Bowers, 2010). Other studies have shown that the closure of streets can lead to a reduction in crime levels (Zavoski et al, 1999). Johnson and Bowers (2010) found that crime rates were highest amongst those streets with the greatest number of connections to other streets.…”
Section: Neighbourood Layoutmentioning
confidence: 99%